Philippine industry yearbook of labor statistics, 1996. (Department of Labor and Employment, Bureau of Labor and Employment Statistics, 1996)
Purpose: It "presents industry-specific information useful to planners both in government and in the private sector. Offers vital information on industry performance upon which investment priority decisions are shaped."